A cost - Ghahnavieh, Abbas Rajabi (Journal of electrical engineering & technology)
Available transfer capability (ATC) is a measure of the transfer capability remaining in a transmission system. Application of unified power flow controllers (UPFCs) could have positive impacts on the ATC of some paths while it might have a negative impact on the ATC of other paths. This paper presents an approach to evaluate the impacts of UPFCs on the ATC from a cost/worth point of view. The UPFC application worth is considered as the maximum cost saving in enhancing the ATC of the paths due to the UPFC implementation. The cost saving is considered as the cost optimal application of other system reinforcement alternatives to reach the same ATC level obtained by UPFC application.